Prevalência da pancreatite crônica em pacientes portadores de cirrose hepática alcoólica: estudo histopatológico - Santos, Júlia de Fátima Gonçalves (2016)
Objective To evaluate the prevalence of chronic pancreatitis (CP) in alcoholic liver cirrhosis patients (ALC) based on the histopathological features. Subjects - We retrospectively analyzed the autopsies of 25 patients with alcoholic liver cirrhosis, eighteen men and seven women, mean age (standard desviation) of 47.2 ± 13.8 years, range from 24 to 83 years. The daily alcohol consumption was 239.6 ± 155.3 g in average, and the mean duration of alcohol abuse was 16.7 ± 7.2 years. A control group was composed of ten men, mean age of 43.1 ± 21.8 years, range from 22 to 77 years, without liver cirrhosis submitted to obligatory autopsies because of violent deaths. Methods - Liver cirrhosis histopathological diagnosis was based on the findings of systemized fibrosis with septa formation delimiting nodules of varied sizes and unspecific chronic inflammation. Chronic pancreatitis histopathological diagnosis was based, especially, on the identification of foci of exsudate of lymphocytes, histiocytes and, eventually, plasma cells (called mononuclear cell infiltration) around the ducts and in the inter and intralobular conjunctive tissue. The CP was classified as mild when it had discrete mononuclear infiltrated (MI) in periductal, interlobular or intralobular area, eventually with the presence of thin strands of fibrosis; moderate pancreatitis was defined by the increase of the exudate and fibrosis intensity, occasionally associated with small ducts dilatation. The severe form of the CP was characterized by MI, dense fibrosis with or without calculi in the ducts, irregular ductal dilatation, glandular (acinar) atrophy and, sometimes calcification. Results - CP was obeserved in the 25 patients (100%) with ALC, considered mild in 18 (72%), moderate in two (8%) and severe in five (20%). In the control group two out of the ten (20%) had mild chronic pancreatitis. Conclusion - Chronic pancreatitis is frequently associated with the alcoholic liver cirrhosis, with the mild form predominance.